The application of coffee husk ash to improve compaction characteristics of clay soil. Issue 1 (1st February 2023) - Munirwan, R P; Mohd Taib, A; Taha, M R; Abd Rahman, N; Munirwansyah, M
Abstract: Soil stabilization is the modification process of one or more soil properties mechanically or chemically to generate an improved soil material with the appropriate engineering properties. Recently, stabilization methods utilizing commonly used stabilizing agents are becoming more costly. On the other hand, there is an increasing interest in identifying new green technologies that may be used to improve construction practices. As a result, the search for new materials and improved processes for processing local materials has moved to a priority. Thus, this study was conducted to validate the effectiveness of coffee husk ash (CHA) as a stabilizing agent on the compaction characteristics of clayey soil. To characterize the properties of clayey soil admixed with varying concentrations of CHA, Atterberg limits, grain size distribution, and standard proctor compaction tests were conducted. The soil was mixed with CHA in concentrations ranging from 5% to 25% by dry weight of the soil. Observation indicates CHA progressively enhances soil compaction performance. The pozzolanic and hydration reactions between CHA and the soil may have made the soil more likely to be compacted.